Application of dermoscopy in diagnosis of seborrheic keratosis, actinic keratosis and basal cell carcinoma - Hao-bo JIANG; Zhi-ping SUN; Hai-zhen CHEN; Ping-hua LIU; Wen-zhi SHI; Shao-yan DAI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To explore the value of dermoscopy in the diagnosis of seborrheic keratosis, actinic keratosis and basal cell carcinoma. Methods: Patients which clinically diagnosed as seborrheic keratosis (108 cases), actinic keratosis (46 cases) and basal cell carcinoma (71 cases) were enrolled, and their clinical data, clinical pictures, dermoscopic diagnosis and pathological findings were collected. The sensitivity, specificity and consistency of dermoscopy in the diagnosis of these three diseases were analyzed. Results: The consistency, sensitivity, specificity, misdiagnosis rate, missed diagnosis rate, Youden index and Kappa index were reported as followings: ①for seborrheic keratosis, were 93.52%、93.52%, 94.67%、93.33%, 90.91%、93.94%, 9.09%、6.06%, 5.33%、6.67%, 85.58%、87.27%, 0.8484、0.8511, respectively. ②for actinic keratosis, were 89.13%、89.13%, 88.89%、85.19%, 89.47%、94.74%, 10.53%、5.26%, 11.11%、14.81%, 78.36%、79.93%, 0.7776、0.7809, respectively. ③for basal cell carcinoma, were 91.55%、91.55%, 89.74%、92.31%, 93.75%、90.63%, 6.25%、9.37%, 10.26%、7.69%, 83.49%、74.84%, 0.8304、0.8293, respectively. Conclusion: The application of dermoscopy in the diagnosis of seborrheic keratosis, actinic keratosis and basal cell carcinoma has a high diagnostic value, which is worthy of clinical application.